Pemahaman Makna Keluarga Sakinah Mawaddah Warahmah dan Pembentukannya Bagi Pelaku Pernikahan Dibawah Umur di Kecamatan Enggano Kabupaten Bengkulu Utara - Mardhiyah, Husna; Suryani, Suryani; Fahimah, Iim (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2024)
Abstract : This research aims to narrate the understanding of the concept of the sakinah family for perpetrators of underage marriages in Enggano District, North Bengkulu Regency and its implementation for perpetrators of underage marriages in Enggano District, North Bengkulu Regency. This research is a type of qualitative research, namely a research process that produces descriptive data in the form of written or spoken words from the people interviewed and the behavior observed, where the descriptive data is data collected in the form of words, pictures and not numbers. The results of this research show that the understanding of the concept of sakinah mawaddah warahmah family among early marriage couples in Enggano District, North Bengkulu Regency is understood by various opinions, namely a family founded on love, a family where everyone respects each other and can overcome difficulties in a family way and live in harmony. , a family that is able to create a religious life within the family, accept the strengths and weaknesses of a partner and complement and understand each other, a family that is happy and has time to gather and communicate with each other. The implementation of the sakinah mawaddah warahmah household concept for underage marriage actors in Enggano District, North Bengkulu Regency is as fulfilling each other's rights and obligations as husband and wife, mutual trust, forgiving each other, understanding and advising each other, giving each other love.Keywords: Underage marriage, implementation, sakinah family. Abstrak: Penelitian ini bertujuan untuk menarasikan pemahaman konsep keluarga sakinah pada pelaku pernikahan dibawah umur di Kecamatan Enggano Kabupaten Bengkulu Utara dan implementasinya bagi pelaku pernikahan dibawah umur di Kecamatan Enggano Kabupaten Bengkulu Utara. Penelitian ini termasuk jenis penelitian kualitatif yaitu suatu proses penelitian yang menghasilkan data-data deskriftif yang berupa kata-kata tertulis atau lisan dari orang-orang yang diwawancarai dan prilaku yang diamati, dimana data-data deskriftif tersebut merupakan data yang dikumpulkan berupa kata-kata, gambar dan bukan angka. Hasil dari penelitian ini menunjukkan bahwa pemahaman konsep keluarga sakinah mawaddah warahmah pada pasangan perkawinan usia dini di Kecamatan Enggano Kabupaten Bengkulu Utara dipahami dengan berbagai pendapat yaitu keluarga yang didirikan atas dasar cinta, keluarga yang setiap orangnya saling menghormati dan bisa mengatasi kesulitan secara kekeluargaan dan hidup rukun, keluarga yang mampu menciptakan kehidupan religius dalam keluarga, menerima kelebihan dan kekurangan pasangan serta saling melengkapi dan memahami, keluarga yang bahagia dan punya waktu untuk berkumpul dan saling berkomunikasi.   Adapun implementasi konsep rumah tangga sakinah mawaddah warahmah bagi pelakum pernikahan dibawah umur di Kecamatan Enggano Kabupaten Bengkulu Utara adalah sebagai Saling memenuhi hak dan kewajiban sebagai suami dan istri, Saling Percaya, Saling Memaafkan, Saling Mengerti dan menasehati,  Saling memberi kasih sayang.Kata Kunci: Pernikahan dibawah umur, Implementasi, Keluarga sakinah.